Small Bowel Obstruction due to Mesodiverticular Band of Meckel's Diverticulum: A Case Report - Aziz Sumer; Ozgur Kemik; Aydemir Olmez; A. Cumhur Dulger; Ismail Hasirci; Umit Iliklerden; Erol Kisli; Cetin Kotan (Case Reports in Medicine)
Meckel's diverticulum is the most common congenital anomaly of the small intestine. Common complications related to a Meckel's diverticulum include haemorrhage, intestinal obstruction, and inflammation. Small bowel obstruction due to mesodiverticular band of Meckel's diverticulum is a rare complication. Herein, we report the diagnosis and management of a small bowel obstruction occurring due to mesodiverticular band of a Meckel's diverticulum.